2022
DOI: 10.1108/ijrdm-06-2022-0186
|View full text |Cite
|
Sign up to set email alerts
|

Is the whole greater than the sum of its parts? A vending retail study

Abstract: PurposeThis study aims to identify which elements of the vending marketing mix are the main sources of competitive advantage for the industry, how they impact vending profitability, and what are their related synergistic effects.Design/methodology/approachA full factorial experiment was developed to determine the effect of eight marketing mix scenarios on the profitability of a new vending channel in a French university library and assess the synergistic effects among three elements of a marketing mix (i.e. pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…, 2020, Table 1). However, based on the idea that the whole is greater than the sum (Stoyanov, 2023) and taking the synergy between innovation and sustainability into account, our current study goes further. We point out that it is possible to define a unique construct, SOCI, combining innovation and sustainability in a multidimensional concept and which simultaneously influences consumer satisfaction with commercial settings.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…, 2020, Table 1). However, based on the idea that the whole is greater than the sum (Stoyanov, 2023) and taking the synergy between innovation and sustainability into account, our current study goes further. We point out that it is possible to define a unique construct, SOCI, combining innovation and sustainability in a multidimensional concept and which simultaneously influences consumer satisfaction with commercial settings.…”
Section: Discussionmentioning
confidence: 90%
“…Secondly, the literature in retail has already shown that either innovation or sustainability or both, as independent variables, are factors that generate competitive advantages for retail businesses (Fuentes-Blasco et al, 2017; Mar ın-Garc ıa et al, 2020, Table 1). However, based on the idea that the whole is greater than the sum (Stoyanov, 2023) and taking the synergy between innovation and sustainability into account, our current study goes further. We point out that it is possible to define a unique construct, SOCI, combining innovation and sustainability in a multidimensional concept and which simultaneously influences consumer satisfaction with commercial settings.…”
Section: Sustainabilityoriented Commerce Innovationmentioning
confidence: 93%
See 1 more Smart Citation
“…These authors point out the importance of measuring these dimensions as a global variable, where the effect of one dimension stimulates another and vice versa, also adapting their analysis to the different economic sectors to capture the specificity that characterizes them (Calabrese et al, 2021). In the context of marketing, the literature also indicates that the result obtained when considering the variables as a whole may be greater than when done individually (Kehal & El Alfy, 2021; Stoyanov, 2023). The IPMA thus prioritizes the factors identified by generating an index, but simultaneously relating all the factors to each other, which directs the retailer's management toward priority areas, taking into account the information related to all the factors involved in SOI‐r.…”
Section: Discussionmentioning
confidence: 99%